Facebook and the others. Potentials and obstacles of Social Media for teaching in higher education. (April 2016) - Manca, Stefania; Ranieri, Maria
Abstract: Social Media tools are seen by many authors as powerful drivers of change for teaching and learning practices, in terms of openness, interactivity and sociability. However, extensive surveys about actual use that are carried out with large samples at a national level are rare. This study reports the results of a survey addressed to the Italian academic staff, with the aim of identifying the uses of Social Media in the field of university teaching practices. The response rate was 10.5%, corresponding to 6139. The respondents were asked to identify frequency of use, motivations, teaching practices and obstacles related to the use of a number of tools: generic social network sites (Twitter, Facebook), professional and academic networking services (LinkedIn, ResearchGate andAcademia.edu ), tools to write and comment (blogs, wikis) and to archive and retrieve content material for lectures and group work (podcasts, YouTube and Vimeo, SlideShare). Analyses of data tested which socio-demographic variables mostly affected frequency of use, and the relationships between motivations, ways of use, barriers to use and the scientific discipline. The results show that Social Media use is still rather limited and restricted and that academics are not much inclined to integrate these devices into their practices for several reasons, such as cultural resistance, pedagogical issues or institutional constraints. However, there are differences among academics in the ways they use Social Media or perceive them, mostly depending on the scientific discipline of teaching. Overall, the results emphasise ambivalent attitudes towards the benefits and challenges of Social Media in the context of higher education with obstacles prevailing over advantages. Highlights: We examine the frequency of use of Social Media for teaching purposes. The variable most associated with frequency of use is scientific discipline. We present motivations and ways to use Social Media tools in teaching. A principal component analysis reveals three main factors as obstacles to use. Results show a complex scenario where potentials and barriers are intertwined.